Impacts of Atmospheric CO2 and Soil Nutritional Value on Plant Responses to Rhizosphere Colonization by Soil Bacteria - Williams, Alex; Pétriacq, Pierre; Beerling, David J.; Cotton, T. E. Anne; Ton, Jurriaan (Frontiers in Plant Science, 2018)
Concerns over rising atmospheric CO2 concentrations have led to growing interest in the effects of global change on plant-microbe interactions. As a primary substrate of plant metabolism, atmospheric CO2 influences below-ground carbon allocation and root exudation chemistry, potentially affecting rhizosphere interactions with beneficial soil microbes. In this study, we have examined the effects of different atmospheric CO2 concentrations on Arabidopsis rhizosphere colonisation by the rhizobacterial strain Pseudomonas simiae WCS417 and the saprophytic strain Pseudomonas putida KT2440. Rhizosphere colonisation by saprophytic KT2440 was not influenced by sub-ambient (200 ppm) and elevated (1,200 ppm) concentrations of CO2, irrespective of the carbon (C) and nitrogen (N) content of the soil. Conversely, rhizosphere colonisation by WCS417 in soil with relatively low C and N content increased from sub-ambient to elevated CO2. Examination of plant responses to WCS417 revealed that plant growth and systemic resistance varied according to atmospheric CO2 concentration and soil-type, ranging from growth promotion with induced susceptibility at sub-ambient CO2, to growth repression with induced resistance at elevated CO2. Collectively, our results demonstrate that the interaction between atmospheric CO2 and soil nutritional status has a profound impact on plant responses to rhizobacteria. We conclude that predictions about plant performance under past and future climate scenarios depend on interactive plant responses to soil nutritional status and rhizobacteria.